1996
DOI: 10.1016/0304-3959(95)00188-3
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral analgesic effect of intra-articular clonidine

Abstract: Sympathetic nervous system stimulation, which releases noradrenaline, influences the nociceptor activity which develops after tissue injury. The alpha 2-adrenergic agonist, clonidine, produces analgesia through a central mechanism but also inhibits noradrenaline release at terminal nerve fibre endings. Clonidine may induce analgesia when administered at peripheral sites. This study assesses the potential analgesic effect of clonidine after intra-articular administration. Forty ASA I-III patients, scheduled for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(96 citation statements)
references
References 17 publications
6
85
0
5
Order By: Relevance
“…28 Moreover, intra-articular administration of a low dose of an a 2 -adrenoceptor agonist significantly attenuated postoperative pain by surgery of the knee joint in humans. 29 In arthritic mice, a knockout of the a 2A -adrenoceptor or intraarticular, but not intrathecal administration of an a 2 -adrenoceptor antagonist, reversed the antihyperalgesic effect induced by transcutaneous electrical stimulation: 30 this finding suggests that the a 2A -adrenoceptor is involved in mediating the pain suppressive effect induced by transcutaneous electrical stimulation. It has been hypothesized that release of opioids from cutaneous immune cells may be mediating pain suppressive effect of norepinephrine in the inflamed skin of rats.…”
Section: B Antinociceptive Role Of 2 -Adrenoceptorsmentioning
confidence: 91%
“…28 Moreover, intra-articular administration of a low dose of an a 2 -adrenoceptor agonist significantly attenuated postoperative pain by surgery of the knee joint in humans. 29 In arthritic mice, a knockout of the a 2A -adrenoceptor or intraarticular, but not intrathecal administration of an a 2 -adrenoceptor antagonist, reversed the antihyperalgesic effect induced by transcutaneous electrical stimulation: 30 this finding suggests that the a 2A -adrenoceptor is involved in mediating the pain suppressive effect induced by transcutaneous electrical stimulation. It has been hypothesized that release of opioids from cutaneous immune cells may be mediating pain suppressive effect of norepinephrine in the inflamed skin of rats.…”
Section: B Antinociceptive Role Of 2 -Adrenoceptorsmentioning
confidence: 91%
“…Both an intrinsic analgesia (Gentili et al, 1996; and augmentation of analgesia produced by bupivacaine (Reuben and Connelly, 1999;Joshi et al, 2000) and morphine (Buerkle et al, 2000) have been reported. Clonidine has been injected into the inflamed knee joint of rodents in preclinical trials, and analgesia was observed to be enhanced by inflammation .…”
Section: G ␣-Adrenoceptor Agonistsmentioning
confidence: 99%
“…[13][14][15] Various preclinical and clinical studies have reported that clonidine produces antinociception regardless of the route of administration (central or peripheral). [16][17][18][19] Topical administration of clonidine elicits antinociception by blocking the emerging pain signals at peripheral terminals through alpha 2 adrenoceptors without producing the undesirable central side effect observed after systemic administration. 20 In a dose response study, it was demonstrated that iv clonidine 3µg/kg was more effective than clonidine 2µg/kg for postoperative pain relief after hemilaminectomy, while clonidine 5µg/kg resulted in same analgesia with significant side effects.…”
Section: Introductionmentioning
confidence: 99%